Bridging Cultural Diversity Gaps at Luhonono Police Station: Police Leadership Role - Mabuku, Kennedy Kaumba (UIN Sunan Gunung Djati Bandung, 2023)
This study investigates the pivotal role of police leadership in mitigating cultural diversity gaps within the Luhonono Police Station, utilizing an exploratory qualitative approach. The study's sample comprises four police leaders with station experience and five non-management police officers. Data collection involves individual semi-structured interviews, recorded to aid data interpretation, with thematic analysis employed for data analysis. The findings underscore the significance of effective police leadership in improving relationships, minimizing turnover, ensuring fairness in decision-making, enhancing performance, and motivating the police force. The study recommends that the selection of police leaders should prioritize their commitment to embracing cultural diversity. Furthermore, it advocates for the development of policies supporting cultural diversity, provision of training, and promotion of awareness among the team to foster an inclusive and respectful workplace. The study argues that, although police leaders play a pivotal role in addressing cultural diversity, their effectiveness is impeded without standardized institutional policies or strategies to manage such issues.